SEMIOTIC ANALYSIS OF THE MEANING OF FALLING IN LOVE IN THE LYRICS OF THE SONG "ASMALIBRATION" BY SOEGI BORNEAN - Syafruddin Pohan; Fairuz Raniah Adiba Putri; Anisya Hafila Hartono (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
The purpose of making this journal is to find out the meaning of the lyrics of the song "Asmalibrasi" then the next goal is to find out what meaning is contained in the lyrics of the song "Asmalibrasi" and some of our goals, especially this song is specifically for teenagers who are in love trying to continue to the next stage. more serious, namely marriage, but the couple had doubts because of the many problems that arose, but the couple was finally able to proceed to the marriage stage because by lowering their respective egos. The theory that we use is according to some well-known experts. The method we use in this journal is by listening to songs and reading the lyrics of the songs. The results of our analysis show that each of the lyrics of the song "Asmalibrasi" contains many meanings that we must learn. Our recommendation is to be careful in choosing each partner, not because of societal standards. The meaning expressed is the meaning of denotation, connotation, and myth. In this study, Roland Barthes' semiotic theory is used to explain the denotation, connotation, and myth of the meaning of "Fall in Love" contained in the lyrics of the song. The research method used is an interpretive qualitative method or an inductive way of thinking, namely a way of thinking from the specific to the general. The data collection technique used is document study, namely tracing and obtaining from various sources where the required data is contained. The results of a semiotic study of the lyrics of the song "Asmalibrasi" are as follows. The meaning of the denotation of the lyrics of the song "Asmalibrasi" is Telling about the desire to be immediately married by a lover, this song also contains a deep message full of meaning.